2020
DOI: 10.1186/s12889-020-08667-9
|View full text |Cite
|
Sign up to set email alerts
|

Differences in smokers’ awareness of the health risks of smoking before and after introducing pictorial tobacco health warnings: findings from the 2012–2017 international tobacco control (ITC) Netherlands surveys

Abstract: Background As of May 2016, pictorial health warnings (PHWs) showing the harms of smoking were implemented in the European Union. After one year they had to be fully implemented. We studied changes in awareness of the health risks of smoking after implementation of PHWs among smokers from the Netherlands, whether the trend before the implementation changed after the implementation, and whether there were differences between subgroups. Methods We used survey data from six yearly waves of the International Tobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…This is supported by Al-Azri et al, (2014) and Schliemann et al, (2020) which mentioned smoking as the highest risk factor for cancer. The public generally has a high level of knowledge of the dangers of smoking due to ongoing campaigns to raise awareness about smoking's consequences on people's health (Van Mourik, 2020). An unhealthy diet was the second most identified risk factor (37.2%) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by Al-Azri et al, (2014) and Schliemann et al, (2020) which mentioned smoking as the highest risk factor for cancer. The public generally has a high level of knowledge of the dangers of smoking due to ongoing campaigns to raise awareness about smoking's consequences on people's health (Van Mourik, 2020). An unhealthy diet was the second most identified risk factor (37.2%) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Cognition [22,26,35,47,52] involves factors related to an individual's capacity to absorb and understand a HII's message. Cantrell et al .…”
Section: Resultsmentioning
confidence: 99%
“…Springvloet et al [47] suggested that educational differences may have affected their participants' awareness and memory of the HII message, which could explain why it was ineffective among those from low-SES groups. Similarly, Van Mourik et al [52] suggest that more-educated individuals have more experience with health information, and thus understand it better. The central argument of these studies, thus, is that low-SES individuals generally have more difficulties to understand or absorb the HII message.…”
Section: Thematic Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…Noticing health warning labels on cigarette packages has been associated with increased cognition about the harms of smoking [28][29][30][31][32][33] Health Organization to help countries controlling the smoking epidemics worldwide 1 .…”
Section: Discussionmentioning
confidence: 99%